The Impact of Industrialization on Social Mobility in Rural Communities in Alla District, Enrekang Regency - JS, Nur Alfiah; Kamaruddin, Syamsu A; Awaru, A. Octamaya Tenri (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study is to analyze the impact of industrialization on social mobility in rural communities in Alla District, Enrekang Regency. The research method used is qualitative with a phenomenological approach. Data collection techniques used are in-depth interviews and observations. The results of the study indicate that industrialization has a significant impact on social mobility in society, especially in terms of employment and social status.